Coach Carter - Carter, Thomas, 1953-; Robbins, Brian, 1963-; Tollin, Michael; Gale, David; Schwahn, Mark.; Gatins, John.; Jackson, Samuel L.; Ri'chard, Robert, 1983-; Brown, Rob, 1984-; Ashanti, 1980-; Morgan, Debbi, 1956-; Laresca, Vincent; et al. (Hollywood, Calif. : Paramount Pictures, 2005)
Inspired by a true story, this inspirational account of a high school basketball coach who received high praise, and staunch criticism, for benching his entire undefeated team due to their poor academic performances.
Originally released as a motion picture in 2004.
Inspired by the life of Ken Carter.
Special features include: 2 featurettes "Coach Carter, the man behind the movie" and "Fast break at Richmond High", 6 deleted scenes, and "Hope" music video.
Director of photography, Sharone Meir ; editor, Peter Berger ; music, Trevor Rabin ; costume designer, Debrae Little ; production designer, Carlos Barbosa.
Samuel L. Jackson, Robert Ri'chard, Rob Brown, Ashanti, Debbi Morgan, Vincent Laresca, Rick Gonzalez, Antwon Tanner, Nana Gbewonyo, Channing Tatum.
MPAA rating: PG-13; for violence, sexual content, language, teen partying and some drug material.
Keywords: Carter, Ken -- Drama; African American basketball coaches -- California -- Los Angeles -- Drama; Basketball players -- California -- Los Angeles -- Drama; High school athletes -- Conduct of life -- Drama; Motivation in education -- Drama; Sports films; Fiction films; Feature films; Video recordings for the hearing impaired; Feature films -- United States; Feature films -- Germany